EVALUATION OF IMPLEMENTATION CHARACTER EDUCATION IN SCHOOL CULTURE - Siti NURAENI (Journal of Education and Leadership in Education, 2020)
This evaluation aimed to finding the context of the implementation of the Character Education Program at the Integrated Islamic Junior High School Pondok Duta Cimanggis Depok, readiness of students, educators and educational personnel, facilities and infrastructure, the process of implementing character education programs, and the achievement of program implementation. The method in this evaluation using descriptive qualitative method by looking at empirical data and facts, and the model used the CIPO model (Context, Input, Process, and Output). Data retrieval was carried out scientifically included observation, structured interviews, and documentation. Interviews were conducted with the Principal, Deputy Head of the Curriculum Division, Deputy Head of Facilities and Infrastructure, Deputy Head of Responsible Affairs, Committees, Parents and Students. Then the data obtained was analyzed using the source triangulation method, data display, and conclusion. The conclusion of the evaluation research, While in the process of implementing character education programs there are obstacles including: facilities and infrastructure as well as time that is less supportive in implementingcharacter education. Although in the implementation was founded obstacle, the implementation of the character education program at Pondok Duta Islamic Middle School for the 2017/2018 Academic Year continued to run optimally because these obstacles could be overcome properly. The implication of the implementation of this student character education program was to measure the level of learning achievement of students, especially those related to the behavior of students. It is hoped that schools will be more ready in preparing for this character education program.